Description of Knowledge, Attitudes, and Actions about Regarding Occupational Health and Safety in D-IV Students Health Analysts, Nahdlatul Ulama University, Surabaya - Fauzi, M.; Nourma Rhomadhoni, Muslikha; Wijaya, Satria; Handayani, Dwi (Rifa'Institute, 2023)
Introduction: The application of OHS (Occupational Health and Safety) culture is very important as an effort to prevent work accidents in the work environment. The implementation of OHS at the University must be carried out, because the University is a busy place and is a means of studying. Major of Health Student was spent 70% in laboratories from all study. Objective: The purpose of this study is to describe knowledge, attitudes, and actions about health and safety. Occupational Safety for UNUSA Health Analyst D-IV Study Program students. This study used a descriptive research design with an observational quantitative approach with a cross sectional design. Method: This study uses primary data collected through a questionnaire. The sample of this study was D-IV Health Analyst students, totalling 180 people. Result and Discussion: The results of this study indicate that the level of knowledge of Health Analyst students on good criteria is 69.4%, the positive attitude of Health Analyst students is 77.2% and the positive action of Health Analyst students is 77.2%. Conclusion: The conclusion of this study is that the overall level of knowledge, attitudes, and actions of Health Analyst students on Occupational Health and Safety is good